Food Discipline According to Ayurveda- A Holistic Approach in Eating Healthy Food with Ayurveda Siddhant Mentioned in Ayurveda and Food Technology - Sharma, Nikita; Singh, Chandan; Purvia, Rajendra Prasad; Adhlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2023)
The high end of medical science is the preservation of health and it can be attained in two ways, first of all by eradicating the diseases, which may invade the body, secondly by due observation of such rules as would keep away the disease.Ayurveda elaborate about different dietary regimens including recopies advocated for health promotion, prevention of illness and also prescribed for management of diseases as well which further provide a great scope for the development of nutraceuticals and dietary supplements. Rasayanas are the foods, therapies or practices that are conducive and beneficial to body tissues and its functions. Diet plays an important role in keeping our mind healthy and explicit psycho-pharmacological effects of food led to classification of food in to following 3 categories. 1. Satvik diet: ideal diet containing vegetarian, non-oily, non-spicy articles which are congenial to the body and mind. 2. Rajasik diet: too spicy, hot, sour, salty; excite the mental faculties.3. Tamsik diet: too oily and heavy food. But in the age of systems biology, personalised medicine, and the wider context of a more holistic transition in sciences generally, modern knowledge is reinventing and advancing a number of these ideas. Trans disciplinary study could be important for advancing the fields of food and health sciences as well as for offering real-world remedies for current health issues. This article highlights the need for a deeper engagement with traditional knowledge systems, such as Ayurveda, by quickly reviewing the similarities between Ayurveda and Technology..